Sex differences in the prevalence and risk factors of non-suicidal self-injury behaviors among adolescent outpatients with major depressive disorder - Lv, Guangyou; Ma, Botao; Qi, Siyuan; An, Huimei (Frontiers in Psychiatry, 2025)
ObjectiveAlthough non-suicidal self-injury (NSSI) behaviors are particularly prevalent among adolescent outpatients with major depressive disorder (MDD), few studies have investigated the sex differences in this population. Therefore, this study aimed to investigate sex differences in the prevalence and risk factors of NSSI among adolescent outpatients with MDD.MethodsIn total, 284 adolescent outpatients who met the DSM-V diagnostic criteria for MDD were recruited for this cross-sectional study. A self-designed questionnaire, the Children’s Depression Inventory (CDI), Chinese version of the Functional Assessment of Self-Mutilation (CFASM), Pittsburgh Sleep Quality Index (PSQI), and Adolescent Self-Rating Life Events Checklist (ASLEC) were employed to assess participants’ socio demographic factors, depressive symptoms, NSSI behaviors, sleep quality, and stressful life events, respectively.ResultsThe prevalence of NSSI behaviors was significantly higher in female adolescents than in male adolescents. Notably, female adolescents demonstrated significantly higher NSSI functioning scores, NSSI frequency, and CDI scores than male adolescents. Regression analysis showed that among female adolescents, higher PSQI and ASLEC scores were identified as significant risk factors for NSSI behaviors, with the frequency of NSSI positively correlated with ASLEC scores. However, these associations were not observed in males.ConclusionNSSI is more prevalent in female adolescent outpatients with MDD than male outpatients with MDD. Further, there are significant sex differences in the risk factors associated with NSSI, suggesting that sex differences should be considered when developing prevention and intervention strategies for coexisting NSSI behaviors among adolescent outpatients with MDD.